2020
DOI: 10.3386/w28148
|View full text |Cite
|
Sign up to set email alerts
|

All Aboard: The Effects of Port Development

Abstract: and a team of Columbia University undergraduate students provided outstanding research assistance. César gratefully acknowledges financial support from the ERC (Starting Grant 'World Seastems' No. 313847). Réka is grateful for financial support from the Provost's Office at Columbia. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Table 5 shows a highly significant negative correlation between the control function “predicted household rent in/out rate” and the potential endogenous variable “whether the household participates in the land rental market”. A possible reason is that the farmland resources in the prefecture-level city are limited, and the land rental behavior of other villages crowds out the village farmland demand [ 34 ]. The results for the Hhlandin_cf and Hhlandoff_cf both show that the control functions included in the production efficiency equation are significant.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 shows a highly significant negative correlation between the control function “predicted household rent in/out rate” and the potential endogenous variable “whether the household participates in the land rental market”. A possible reason is that the farmland resources in the prefecture-level city are limited, and the land rental behavior of other villages crowds out the village farmland demand [ 34 ]. The results for the Hhlandin_cf and Hhlandoff_cf both show that the control functions included in the production efficiency equation are significant.…”
Section: Resultsmentioning
confidence: 99%
“…1 The tractability of our approach is evinced by the number of recent working papers who have proposed extensions to it since its original dissemination. These include extending the framework to consider multiple types of transportation networks and transshipment (as in Fan, Lu, and Luo (2019) and Fan and Luo (2020), respectively), extending the framework to include endogenous development of transportation capabilities in locations (as in Ducruet, Juhász, Nagy, Steinwender, et al (2020)), and extending the framework to multiple sectors with economies of scale in traffic rather than traffic congestion (as in Ganapati, Wong, and Ziv (2020)).…”
Section: Optimal Routing In Two Spatial Modelsmentioning
confidence: 99%
“…Other technologies, in particular automation technology like robots (Graetz and Michaels, 2018;Acemoglu and Restrepo, 2020), and trade (Autor et al, 2016) have been shown to be important factors in explaining employment trends. Given the strong geographic concentration of the manufacturing sector, and the potential spatial impact of changes in trade technology (Ducruet et al, 2019), these are complementary mechanisms that a↵ect not only the aggregate changes in employment, but also the distribution of jobs in space. Furthermore, the long-run e↵ects of technology may also work through the interaction with labor supply by changing skill accumulation and education decisions as in Dvorkin and Monge-Naranjo (2019).…”
Section: The Rise Of It In the Estimated Modelmentioning
confidence: 99%